Analysis on Treatment Effect of Mine Tunnel Construction Spring in Karst Area. (5th April 2021) - Liu, Bocheng; Ye, Wenlong; Zhu, Chunming; Chen, Ran; Huang, Songxian; Ni, Xiaodong
Abstract : The investigation of ultrashallow buried mining method in an interval revealed the existence of the karst fracture zone. The flow rate of 9 springs exposed in the initial excavation was relatively large, and the total water output per hour was nearly 300 m 3 . The filling materials in karst channels or fissures had the risk of bursting during excavation. Moreover, the ultrashallow buried tunnel undercrossed a special railway line, and the construction required higher surface deformation control. In view of the abovementioned risk problems, based on the grouting ideas of "assessment of influence, " "determination of surrounding rock, " "zone positioning, " and "dynamic grouting, " the grouting design scheme is dynamically optimized, and the grouting construction of surrounding water is cut off. Combined with the tunnel inspection, monitoring data, and numerical analysis, it is verified that the construction technology adopted in the project can ensure the stability of the project, which can provide a reference for similar projects.